Bacillus xiamenensis Inhibits the Growth of Moraxella osloensis by Producing Indole‐3‐Carboxaldehyde - Masahiro Watanabe; Yuika Sekino; Kouji Kuramochi; Yuuki Furuyama (MicrobiologyOpen)
ABSTRACT Moraxella osloensis, a gram‐negative rod‐shaped bacterium found on human skin, produces 4‐methyl‐3‐hexenoic acid, contributing to clothing and body malodor. M. osloensis is resistant to UV light, drying, and antimicrobials, making its eradication challenging. As the skin is low in nutrients, commensal bacteria compete for resources and use diverse strategies to inhibit their competitors. Therefore, skin‐derived bacteria that exhibited growth‐inhibitory activity against M. osloensis were searched. Screening skin‐derived bacteria using a coculture halo assay revealed that Bacillus xiamenensis formed an inhibition zone with M. osloensis. Coculture plates were extracted with ethyl acetate and fractionated using a silica gel column and preparative thin‐layer chromatography to isolate the active compound from the B. xiamenensis metabolites. Nuclear magnetic resonance spectroscopy identified the active compound as indole‐3‐carboxaldehyde, which has low toxicity in humans. At soluble concentrations, indole‐3‐carboxaldehyde does not inhibit the growth of other bacteria, such as Staphylococcus aureus, Escherichia coli, and Bacillus subtilis, suggesting M. osloensis is highly sensitive to indole‐3‐carboxaldehyde. These findings highlight B. xiamenensis as a promising candidate for the development of a skin probiotic to promote skin health and combat malodor‐causing bacteria.